Semiconductor-metal-semiconductor TiO2@Au/g-C3N4 interfacial heterojunction for high performance Z-scheme photocatalyst - Hong, Tingkai; Anwer, Shoaib; Wu, Ju; Deng, Chonghai; Qian, Hongmei (Frontiers in Chemistry, 2022)
We designed an edge-sites 2D/0D/2D based TiO2@Au/g-C3N4 Z-scheme photocatalytic system consists of highly exposed (001) TNSs@Au edge-site heterojunction, and the Au/g-C3N4 interfacial heterojunction. The designed photocatalyst was prepared by a facile and controlled hydrothermal synthesis strategy via in-situ nanoclusters-to-nanoparticles deposition technique and programable calcination in N2 atmosphere to get edge-site well-crystalline interface, followed by chemically bonded thin overlay of g-C3N4. Photocatalytic performance of the prepared TNSs@Au/g-C3N4 catalyst was evaluated by the photocatalytic degradation of organic pollutants in water under visible light irradiation. The results obtained from structural and chemical characterization conclude that the inter-facet junction between highly exposed (001) and (101) TNSs surface, and TNSs@Au interfacial heterojunction formed by a direct contact between highly crystalline TNSs and Au, are the key factors to enhance the separation efficiency of photogenerated electrons/holes. On coupling with overlay of g-C3N4 2D NSs synergistically offer tremendous reactive sites for the potential photocatalytic dye degradation in the Z-scheme photocatalyst. Particularly in the designed photocatalyst, Au nanoparticles accumulates and transfer the photo-stimulated electrons originated from anatase TNSs to g-C3N4via semiconductor-metal heterojunction. Because of the large exposed reactive 2D surface, overlay g-C3N4 sheets not only trap photoelectrons, but also provide a potential platform for increased adsorption capacities for organic contaminants. This work establishes a foundation for the development of high-performance Z-scheme photocatalytic systems.